Assessment of phthalate knowledge, plastic use practices and cheese handling among adults in Jeddah city (Saudi Arabia) - Allily, Rowida; Mouminah, Haneen H. (The North African Journal of Food and Nutrition Research, 2024)
Background: Phthalates are chemical compounds that have the tendency to migrate into food and beverages, thereby leading to negative health consequences. Aims: was to assess the knowledge of phthalates and practices relating to plastic use among adults residing in Jeddah, Saudi Arabia, with an emphasis on cheese wrapped in plastic materials.  Material and Methods: A total of 435 adult participants completed an online questionnaire consisting of three sections 1) socio-demographic characteristics, 2) knowledge-related phthalates, and 3) practices related to plastic use. All collected data were verified and analyzed using the Statistical Package for Social Sciences (SPSS). Results: Our findings revealed that 64.1% of the respondents had poor knowledge regarding plastics and phthalates with gender being a significant factor (p=0.0003). The usage rate of plastic material was found to be remarkably high with 38.2% keeping the purchased cheese either in its original plastic wrapping or placed inside plastic boxes. Moreover, 53.6% never viewed the safe plastic number before purchasing the food products. However Interestingly enough, the type of plastics did not influence participant’s decision-making process when it came down to purchasing or consuming cheese (45.1% & 46.2%, respectively). Respondents who had poor practice represented up to 85 %, while those with poor knowledge and practice constituted 65.1%. However, no significant link between these two factors could be established. Conclusions: Poor awareness levels concerning phthalates along with imprudent usage rates for plastics were observed among adults living within Jeddah city's boundaries; thus, appropriate interventions aimed at raising awareness need implementation so as minimize exposure risks associated with this issue.Keywords: Phthalate, Plastic use, Cheese, Knowledge, Practice, Saudi Arabia.